Analysis of Internal and External Factors Affecting Tax Aggressiveness in The Healthcare Sector Companies - Toly, Agus Arianto (International Journal of Organizational Behavior and Policy, 2024)
This study aims to examine the influence of internal factors (management compensation and company liquidity) and external factors (tax consultant variable) on tax aggressiveness. Using multiple regression analysis, the hypothesis testing results based on 116 panel data observations from the healthcare sector companies listed in the IDX between 2019-2022 indicate that all variables have an impact on the tax aggressiveness of the company, with less consistent directions of influence, especially for company liquidity and tax consultant. Those independent variables influence tax aggressiveness positively, indicating that the more liquid the company and more tax consultants it hires, the higher its aggressiveness. These results were robust to the alternative models of the tax aggressiveness, which each of the independent variables were placed in the models. The practical implication of this study is that tax aggressiveness behavior will not only be triggered by internal factors, but it is possible to be affected by external ones.